2002
DOI: 10.1124/dmd.30.12.1297
|View full text |Cite
|
Sign up to set email alerts
|

Deacylation of N-Arylformamides andN-Arylacetamides by Formamidase in Rat Liver

Abstract: ABSTRACT:The in vitro deacylation of N-arylformamides and N-arylacetamides to arylamines was examined in rat liver preparations. When 2-acetylaminofluorene or 2-formylaminofluorene was incubated with rat liver microsomes or cytosol, the deacylated metabolite, 2-aminofluorene, was formed. The deacylating activity of liver microsomes was inhibited by bis(4-nitrophenyl)phosphate and phenylmethanesulfonyl fluoride, inhibitors of carboxylesterase. In contrast, the activity of liver cytosol was inhibited by diisopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Finally, at least for aryl isocyanide 1 , we demonstrated that formamidine 1NG spontaneously degrades to formamide 1FA . It was previously established that in mammalian liver, N -arylamines can undergo N -acetylation/formylation; on the contrary, the corresponding N -aryl formamides are deformylated in liver cytosol by formamidases, and, to a lesser extent, in microsomes, where carboxylesterases are supposed to play a role …”
Section: Discussionmentioning
confidence: 99%
“…Finally, at least for aryl isocyanide 1 , we demonstrated that formamidine 1NG spontaneously degrades to formamide 1FA . It was previously established that in mammalian liver, N -arylamines can undergo N -acetylation/formylation; on the contrary, the corresponding N -aryl formamides are deformylated in liver cytosol by formamidases, and, to a lesser extent, in microsomes, where carboxylesterases are supposed to play a role …”
Section: Discussionmentioning
confidence: 99%
“…8) Recently, we reported that 2-formylaminofluorene was deformylated to 2-aminofluorene by rat liver formamidase. 24) In this study, we have demonstrated that formamidase also catalyzes the deacylation of N-formylanilines and N-acetylanilines to aniline derivatives, in addition to the N-formylation of anilines to N-formylanilines. Santti and Hopsu-Havu 25) reported that formamidase catalyzed the hydrolysis of formyl-1-aminonaphthalene.…”
Section: Discussionmentioning
confidence: 99%